2020
DOI: 10.1109/access.2020.3000565
|View full text |Cite
|
Sign up to set email alerts
|

A Fast QTMT Partition Decision Strategy for VVC Intra Prediction

Abstract: Different from the traditional quaternary tree (QT) structure utilized in the previous generation video coding standard H.265/HEVC, a brand new partition structure named quadtree with nested multi-type tree (QTMT) is applied in the latest codec H.266/VVC. The introduction of QTMT brings in superior encoding performance at the cost of great time-consuming. Therefore, a fast intra partition algorithm based on variance and Sobel operator is proposed in this paper. The proposed method settles the novel asymmetrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 23 publications
0
79
0
Order By: Relevance
“…Table 4 shows the performance results of the proposed fast algorithm in this paper compared with other fast algorithms. In order to evaluate the performance of the proposed algorithm, we have compared with three fast CU partition algorithms, namely, CTTD [36], FCPD [7], and FPDS [8]. Relative to the anchor method, as can be seen from the table, FCPD has achieved the best encoding quality, the average BDBR of FCPD increased by 0.70%, but the ATS is the smallest compared to other methods, only 34.20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows the performance results of the proposed fast algorithm in this paper compared with other fast algorithms. In order to evaluate the performance of the proposed algorithm, we have compared with three fast CU partition algorithms, namely, CTTD [36], FCPD [7], and FPDS [8]. Relative to the anchor method, as can be seen from the table, FCPD has achieved the best encoding quality, the average BDBR of FCPD increased by 0.70%, but the ATS is the smallest compared to other methods, only 34.20%.…”
Section: Resultsmentioning
confidence: 99%
“…e authors of [8][9][10][11][12][13][14][15][16][17][18][19][20][21] judge texture features by variance or gradient to make skip or early termination. In [8], a gradient method based on texture complexity and gradient-based preprocessing steps are proposed to reduce the number of candidate modes and make early decisions for CU splitting. A fast mode decision algorithm based on gradient is proposed in [9], which calculates the gradient direction and eliminates unnecessary modes based on histogram distribution to reduce the candidate modes before performing the Rough Mode Decision (RMD).…”
Section: Related Workmentioning
confidence: 99%
“…Numerous fast algorithms have been proposed to reduce the coding complexity of VVC. In [14], variance and gradient were utilized to distinguish the large smooth area and complex texture region, and fast partition decision could conduct directly according to these messages. Tang et al [15] used edge features extracted by canny edge detector to skip vertical or horizontal split mode to carry out early termination.…”
Section: Related Workmentioning
confidence: 99%
“…In the digital image processing field, gradient is an excellent indicator to express the feature of image texture. Reference [10], [14] and [15] have shown that gradient is an effective reference in terminating the partition of homogenous CUs and choosing QT split mode directly to deal with CUs with complex texture. Vertical or horizontal split mode can be skipped if the gradient in the other direction is more outstanding.…”
Section: Proposed Algorithm Based On Gradientmentioning
confidence: 99%
“…PU modes and CU combinations [4] are iteratively examined to select the optimal Rate Distortion (RD) cost of CTU [6,17]. Quad tree structure with multi type recursively partitions the slice and generate flexible block sizes [7,8]. In a video encoder, BjøntegaardDelta -Bit Rate (BD-BR) measurement is accustomed to compare the performance.…”
Section: Figure 1 Video Compression Systemmentioning
confidence: 99%